Concrete paideuma and how to dimension the poem - Mejía Blanco, Óscar Humberto (Rastros Rostros, 2015)
Purpose: this article seeks to account for the renewing concerns of language in the Brazilian concrete poetry, delving into the concept of paideuma.Topics: to fulfill this purpose, a review and explanation of the term is included herein, drawing on the proposals made by brothers Augusto and Haroldo de Campos and Decio Pignatari in Olho por olho a olho un (manifiesto).Development: additionally, the poetry of the authors selected and considered by this trio as precursors of new forms, themes, and modes of expression of this Latin American artistic and literary program is explored. Conclusions: thus, the Brazilian concrete poetry involves a change in the use of literary language as it questions the manner in which contents are expressed through some stylistic procedures, dictated from the influential poetic heritage of writers like Joyce, E. E. Cummings and Ezra Pound
Keywords: prismatic idea; purpose of language; paideuma; renovation; verbivoco-visual